2016
DOI: 10.1002/hipo.22611
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin excites hippocampal CA1 GABAergic interneurons at the stratum radiatum-stratum lacunosum moleculare border

Abstract: The hippocampus receives robust serotonergic innervation that is thought to control the excitability of both pyramidal cells and GABAergic interneurons. Previous work has addressed serotonergic regulation of pyramidal cells but considerable gaps remain in our understanding of how serotonin regulates different interneuron subclasses. 5-HT2A receptors (5-HT2ARs) appear to localize predominantly, if not solely, on interneurons in the hippocampus and have been implicated in the regulation of hippocampal function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Giving further support to this idea, Sst interneurons in the somatosensory cortex show increased cFos levels following 5-HT 2A R activation ( Martin and Nichols, 2016 ). Previous studies have reported either 5-HT 2A R-dependent inhibition or 5-HT 2A R-dependent activation of interneurons in the prefrontal cortex (PFC) ( Abi-Saab et al, 1999 ; Ashby et al, 1990 ; Athilingam et al, 2017 ), piriform cortex ( Marek and Aghajanian, 1994 ; Sheldon and Aghajanian, 1990 ), cingulate cortex ( Zhou and Hablitz, 1999 ), cochlear nucleus ( Tang and Trussell, 2017 ), amygdala ( Sengupta et al, 2017 ), olfactory bulb ( Petzold et al, 2009 ; Hardy et al, 2005 ), visual cortex ( Michaiel et al, 2019 ; Azimi et al, 2020 ), and hippocampus ( Wyskiel and Andrade, 2016 ). However, none of these studies identified interneurons using molecular markers, so we do not exclude that different interneuron classes in other cortical areas might mediate the inhibitory downstream effects of 5-HT 2A R. For example, in the PFC a subgroup of PV interneurons has been reported to be activated by this receptor ( Athilingam et al, 2017 ; Puig et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Giving further support to this idea, Sst interneurons in the somatosensory cortex show increased cFos levels following 5-HT 2A R activation ( Martin and Nichols, 2016 ). Previous studies have reported either 5-HT 2A R-dependent inhibition or 5-HT 2A R-dependent activation of interneurons in the prefrontal cortex (PFC) ( Abi-Saab et al, 1999 ; Ashby et al, 1990 ; Athilingam et al, 2017 ), piriform cortex ( Marek and Aghajanian, 1994 ; Sheldon and Aghajanian, 1990 ), cingulate cortex ( Zhou and Hablitz, 1999 ), cochlear nucleus ( Tang and Trussell, 2017 ), amygdala ( Sengupta et al, 2017 ), olfactory bulb ( Petzold et al, 2009 ; Hardy et al, 2005 ), visual cortex ( Michaiel et al, 2019 ; Azimi et al, 2020 ), and hippocampus ( Wyskiel and Andrade, 2016 ). However, none of these studies identified interneurons using molecular markers, so we do not exclude that different interneuron classes in other cortical areas might mediate the inhibitory downstream effects of 5-HT 2A R. For example, in the PFC a subgroup of PV interneurons has been reported to be activated by this receptor ( Athilingam et al, 2017 ; Puig et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior evidence indicates that 5-HT 2A receptor agonists induce EPSPs in the cortex, likely through their expression on excitatory pyramidal neurons ( Aghajanian and Marek, 1999 , Martín-Ruiz et al., 2001 ). In contrast, 5-HT 2A receptor stimulation results in enhanced IPSPs in the hippocampus due to the presence of 5-HT 2A receptors on GABAergic interneurons and ensuing effects on GABA release ( Piguet and Galvan, 1994 , Shen and Andrade, 1998 , Wyskiel and Andrade, 2016 ). This has been suggested to contribute to the effects of 5-HT 2A receptor agonists on activity-dependent gene expression, with a robust increase noted in IEG expression in cortical brain regions and either a decline or no change in the hippocampus ( Benekareddy et al., 2013 , González-Maeso et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the hippocampal CA1 region, the GABAergic interneurons respond to serotonin through 5-HT 2A receptors (5-HT 2A Rs) that stimulate phospholipase Cb that hydrolyzes PtdIns4,5P 2 , resulting in closure of the hyperpolarizing M current. Serotonin also induces membrane depolarization by producing InsP 3 to increase Ca 2+ that stimulates the Ca 2+ -activated nonselective cation current, resulting in membrane excitability (Wyskiel and Andrade, 2016). Dopamine acts through both the D1 and D2 receptors to regulate the formation of cyclic AMP, which also regulates neuronal excitability.…”
Section: Tonic Excitatory Drive and Depressionmentioning
confidence: 99%